The prevalence of MAFLD and its association with atrial fibrillation in a nationwide health check-up population in China - Lei, Fang; Qin, Juan-Juan; Song, Xiaohui; Liu, Ye-Mao; Chen, Ming-Ming; Sun, Tao; Huang, Xuewei; Deng, Ke-Qiong; Zuo, Xiuran; Yao, Dongai; Xu, Li-Juan; Lu, Huiming; et al. (Frontiers in Endocrinology, 2022)
Background and aims The epidemiological characteristics of MAFLD and its relationship with atrial fibrillation (AF) are limited in China. Therefore, we explored the epidemiological characteristics of MAFLD from adults along with the association of MAFLD and 12-ECG diagnosed AF in a nationwide population from health check-up centers. Methods This observational study used cross-sectional and longitudinal studies with 2,083,984 subjects from 2009 to 2017. Age-, sex-, and regional-standardized prevalence of MAFLD was estimated. Latent class analysis (LCA) was used to identify subclusters of MAFLD. Multivariable logistic regression and mixed-effects Cox regression models were used to analyze the relationship between MAFLD and AF. Results The prevalence of MAFLD increased from 22.75% to 35.58% during the study period, with higher rates in males and populations with high BMI or resided in northern regions. The MAFLD population was clustered into three classes with different metabolic features by LCA. Notably, a high proportion of MAFLD patients in all clusters had overweight and prediabetes or diabetes. The MAFLD was significantly associated with a higher risk of AF in the cross-sectional study and in the longitudinal study. In addition, the coexistence of prediabetes or diabetes had the largest impact on subsequent AF. Conclusion Our findings suggested a high prevalence of MAFLD and a high prevalence of other metabolic diseases in the MAFLD population, particularly overweight and glucose dysregulation. Moreover, MAFLD was associated with a significantly higher risk for existing and subsequent subclinical AF in the Chinese population.